Kmetijsko obremenjevanje okolja na Gorenjskih Dobravah v energetski luči - Urbanc, Mimi (Geografski obzornik, 1997)
Extremely intensive diary farming has been developed in Gorenjske Dobrave in the last decades. It has all the features of an industrial production. Although a great impact on the environment would be expected due to large energy inputs, soil and water analyses have not proved any pollution. The article presents the study cases of 3 villages: Goriče, Letenice and Srednja vas.
Keywords: agrarna geografija; Dobrave; Gorenjska; kmetijstvo; onesnaževanje tal; onesnaževanje voda; pokrajinska ekologija; živinoreja